First comparison of French and Australian OsHV-1 mu vars by bath exposure - Burge, Colleen A.; Reecez, Kimberly S.; Dhar, Arun K.; Kirkland, Peter; Morga, Benjamin; Degremont, Lionel; Faury, Nicole; Wippel, Bryanda J. T.; Macintyre, Alanna; Friedman, Carolyn S. (Diseases of Aquatic Organisms, 2020)
Economically devastating mortality events of farmed and wild shellfish due to infectious disease have been reported globally. Currently, one of the most significant disease threats to Pacific oyster Crassostrea gigas culture is the ostreid herpesvirus 1 (OsHV-1), in particular the emerging OsHV-1 microvariant genotypes. OsHV-1 microvariants (OsHV-1 mu vars) are spreading globally, and concern is high among growers in areas unaffected by OsHV-1. No study to date has compared the relative virulence among variants. We provide the first challenge study comparing survival of naive juvenile Pacific oysters exposed to OsHV-1 mu vars from Australia (AUS mu var) and France (FRA mu var). Oysters challenged with OsHV-1 mu vars had low survival (2.5%a exposed to AUS mu var and 10% to FRA mu var), and high viral copy number as compared to control oysters (100% survival and no virus detected). As our study was conducted in a quarantine facility located similar to 320 km from the ocean, we also compared the virulence of OsHV-1 mu vars using artificial seawater made from either facility tap water (3782 mu mol kg(-1) seawater total alkalinity) or purchased distilled water (2003 mu mol kg(-1)). Although no differences in survival or viral copy number were detected in oysters exposed to seawater made using tap or distilled water, more OsHV-1 was detected in tanks containing the lower-alkalinity seawater, indicating that water quality may be important for virus transmission, as it may influence the duration of viral viability outside of the host.